Penelusuran Minat dan Bakat Olahraga pada Siswa Sekolah Menengah Pertama di Kota Semarang Tahun 2019/2020 (Universitas Negeri Semarang, 2021)
The background of this study is the lack of knowledge that schools and teachers have to find out sports talent from students, the suitability of students' interests and talents is not yet known, the lack of knowledge of physical education teachers about talent scouting with themethod. sport search. The research objective: to find out and find the suitability of the sports talent of junior high school students in Semarang City in 2019/2020. Techniques for collecting data used: (1) The aptitude test was sport search used to determine the talents of students, (2) Interviews were used to confirm the results of theaptitude test sports search. The population in this study were junior high school students in the city of Semarang. The sampling technique used purposive random sampling. Data analysis in this study used a descriptive presentse. Data processing usingapplication sports search software. From the results of the data analysis, it was found that a number of 61 students 35.2% of the test participants had interests according to their talents and 112 students or 65.3% of the test participants had interests that did not match their talents. The conclusion is that junior high school students in Semarang City have various sports talents, but some of these potentials do not match the interests of the students. The suggestions from researchers are that the process of scouting and coaching talents can be further improved to optimize student achievement. With this research, he hopes that it will become a reference or alternative for the process of scouting and developing sports talent in the city of Semarang and other areas.